2014
DOI: 10.1108/ebr-03-2013-0055
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization of emerging multinationals: the Latin American case

Abstract: Purpose – The purpose of this paper is to develop an analytical framework that challenges the condescending view of multinationals of emerging countries. In this paper, it is showed that emerging multinational companies (EMNCs) developed valuable resources that leveraged their internationalization strategies. Design/methodology/approach – An exploratory approach was used to investigate the internationalization strategies of EMNCs. A qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…EMMNEs face a number of obstacles when entering foreign markets (Luo and Tung, 2007). They have to deal with: liabilities of foreignness stemming from a lack of legitimacy; liabilities of outsidership due to lack of membership in international networks (Cuervo-Cazurra and Un, 2007); and in some cases, a resource gap relative to advanced countries’ MNEs (Losada-Otálora and Casanova, 2014). …”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…EMMNEs face a number of obstacles when entering foreign markets (Luo and Tung, 2007). They have to deal with: liabilities of foreignness stemming from a lack of legitimacy; liabilities of outsidership due to lack of membership in international networks (Cuervo-Cazurra and Un, 2007); and in some cases, a resource gap relative to advanced countries’ MNEs (Losada-Otálora and Casanova, 2014). …”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This seems to be even more important for emerging market multinational enterprises (EMMNEs), with reverse knowledge transfer (RKT) having arisen as an important issue for these firms. Some authors argue that, in a catch-up attempt, EMMNEs engage in foreign direct investment (FDI) in the pursuit of new knowledge or capabilities which, combined with their existing resources, enable them to compete more effectively with global players (Awate et al , 2015; Bartlett and Ghoshal, 1989; Losada-Otálora and Casanova, 2014; Luo and Tung, 2007). Several authors (Mudambi et al , 2014; Nair et al , 2015; Rabbiosi and Santangelo, 2013) have called for more research on RKT in the EMMNE context.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the empirical studies dealing with this debate focus on EMNEs and DMNEs from a limited set of countries, especially China, India and Brazil (Ciravegna, Fitzgerald and Kundu, 2013;Fleury and Fleury, 2011;Gammeltoft et al, 2010;Matthews, 2006). Moreover, just a limited amount of studies (Bianchi, 2014;Gonzalez-Perez and Velez-Ocampo, 2014;Lopez, Kundu and Ciravegna, 2009;Losada-Otálora and Casanova, 2014) observe multinationals from Latin America (other than the Brazilian and Mexican ones) and Colombian MNEs, which boosts the relevance of this study on Colombian MNEs. Most of these authors have identified gaps in empirical evidences and existing theoretical understanding of the international expansion of firms from Latin America (multilatinas).…”
Section: Introductionmentioning
confidence: 99%
“…When referring to common characteristics among EMNCs, Losada-Otálora and Casanova (2014) affirm that these companies are poor resources-endowed when compared to developed country multinationals and acquisitions are the preferred entry modes. The main purpose of cross-border investments of EMNCs is to overcome resource scarcity, especially technological resources; in other words, the pursue for such resources can be considered a motivation for these companies to operate abroad.…”
Section: -Emerging Market Multinationalsmentioning
confidence: 99%
“…multinationals originating from emerging markets. Even though Brazil is currently considered the ninth largest economy in the word (World Bank, 2016), behind other emerging markets such as China and India, and ahead of some developed countries like Canada and Australia, and Mexico, a country from which some powerful multilatinas arise (Casanova & Fraser, 2009a;Casanova, Fraser & Hoeber, 2009), Brazilian companies still present a cautious and timid behavior when considering their internationalization process (Fleury & Fleury, 2009Borini et al, 2010;Casanova & Fraser, 2009a;Losada-Otálora & Casanova, 2014;Casanova, 2015;Ramamurti, 2012;Melo, 2009, Cyrino & Tanure, 2009, Pattnaik & Kumar, 2014.…”
Section: Abbreviations and Acronymsmentioning
confidence: 99%